Counteracting physical inactivity during the COVID-19 pandemic: Evidence-based recommendations for home-based exercise - Schwendinger, F.; Pocecco, E. (International Journal of Environmental Research and Public Health, 2020)
To reduce transmission of the coronavirus, from its initial outbreak in 2019 up to now, various safety measures have been enacted worldwide by the authorities that have likely led to reduced physical activity levels in the general population. This short communication aims to briefly outline the deteriorative consequences of physical inactivity on parameters of physical fitness and ultimately to highlight associated increases of cardiovascular disease risk and mortality. Finally, evidence-based practical recommendations for exercise that can be performed at home are introduced, to help avoid physical inactivity and therefore maintain or achieve good physical health.